không phải lớp một nha bạn
không phải lớp một nha bạn
Có: \(2a=AE+AF+EF=AE+AF+\sqrt{AE^2+AF^2}\ge\sqrt{AE.AF}\left(2+\sqrt{2}\right)\)
\(\Leftrightarrow\)\(\sqrt{AE.AF}\le\frac{2a}{2+\sqrt{2}}\)\(\Leftrightarrow\)\(\frac{1}{2}AE.AF=\frac{a^2}{3+2\sqrt{2}}\) không đổi
Dấu "=" xảy ra khi \(AE=AF\)\(\Rightarrow\)\(\hept{\begin{cases}2AE+EF=2a\\2AE^2=EF^2\end{cases}}\Leftrightarrow\hept{\begin{cases}EF=2a-2AE\\EF=\sqrt{2}AE\end{cases}}\)
\(\Rightarrow\)\(2a-2AE=\sqrt{2}AE\)\(\Leftrightarrow\)\(AE=\frac{2a}{2+\sqrt{2}}\)
\(x = {-b \pm \sqrt{b^2-4ac} \over 2a}\)
\(x = {-b \pm \sqrt{b^2-4ac} \over 2a}\)
\(x = {-b \pm \sqrt{b^2-4ac} \over 2a}\)
\(x = {-b \pm \sqrt{b^2-4ac} \over 2a}\)
\(x = {-b \pm \sqrt{b^2-4ac} \over 2a}\)
\(x = {-b \pm \sqrt{b^2-4ac} \over 2a}\)1
\(x = {-b \pm \sqrt{b^2-4ac} \over 2a}\)
\(x = {-b \pm \sqrt{b^2-4ac} \over 2a}\)
1+1=